The assessment of drainage performance in the residential area using SWMM - Yuliastuti Juliastuti; Oki Setyandito; Yureana Wijayanti; Lisma Safitri; Timotius Kurniawan Wihartono; Ika Sari Damayanti Sebayang (Universitas Mercu Buana, 2023)
Flood is a general issue that can lead to the life and safety of residents. One of the problems is the lack of capacity in the drainage system in a residential area. This paper will analyze the drainage system based on the capacity in one of the residential clusters. The method for the drainage system performance in hydrology analysis was carried out with Log Person, and the return period for rainfall duration is ten years (R10) for hydraulic analysis using drainage system modeling with EPA – SWMM 5.1. The result based on hydrological is the precipitation for flood forecasting is 159.79 mm. It is found that the drainage capacity is filled in downstream of the main drain with a maximum discharge of 2.726 m3/s and secondary drains with a maximum discharge of 0.624 m3/s. Improvements were made to resolve the insufficiency of the existing channels by running two different scenarios: (1) Re-design the dimensions of the main and secondary channels, (2) Implement a detention pond, as well as re-design the dimensions of the secondary channels. Both scenarios could overcome the flood problem. Scenario 2 shows a higher reduction in the flow discharge at the downstream channel compared to scenario 1.